2020
DOI: 10.1016/j.cortex.2020.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Phantasia–The psychological significance of lifelong visual imagery vividness extremes

Abstract: Visual imagery typically enables us to see absent items in the mind's eye. It plays a role in memory, day-dreaming and creativity. Since coining the terms aphantasia and hyperphantasia to describe the absence and abundance of visual imagery, we have been contacted by many thousands of people with extreme imagery abilities. Questionnaire data from 2000 participants with aphantasia and 200 with hyperphantasia indicate that aphantasia is associated with scientific and mathematical occupations, whereas hyperphanta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
243
2
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(269 citation statements)
references
References 46 publications
21
243
2
3
Order By: Relevance
“…Thus, future investigations should aim to replicate the effect found by Parthasarathi et al (2017) and to give evidence for potential explanations. A promising population within which to address these questions consists of participants with extremely low or high voluntary imagery (aphantasics and hyperphantasics, respectively; Zeman et al, 2020). Moreover, investigating interactions between episodic future thinking and self-report measures of imagery could help to determine the role of imagination abilities in temporal discounting.…”
Section: Future-oriented Cognitive Styles and Imagerymentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, future investigations should aim to replicate the effect found by Parthasarathi et al (2017) and to give evidence for potential explanations. A promising population within which to address these questions consists of participants with extremely low or high voluntary imagery (aphantasics and hyperphantasics, respectively; Zeman et al, 2020). Moreover, investigating interactions between episodic future thinking and self-report measures of imagery could help to determine the role of imagination abilities in temporal discounting.…”
Section: Future-oriented Cognitive Styles and Imagerymentioning
confidence: 99%
“…Fourth, our review of the literature on cognitive styles showed that future studies would benefit from addressing the issue of task complexity. Additionally, a valuable approach would be to extend correlational designs in unselected samples to specific subpopulations with extreme expressions of relevant phenotypes, e.g., aphantasics or hyperphantasics (Zeman et al, 2020). Moreover, combinations of individual differences approaches with experimental challenges may be particularly informative in this context.…”
Section: Limitations and Implicationsmentioning
confidence: 99%
“…In other words, aphantasia is not a monolithic category. Some aphantasics dream vivid dreams, clearly involving conscious visual imagery [76]. But they have problems with the control of conscious visual imagery.…”
Section: Aphantasiamentioning
confidence: 99%
“…Regardless of the exact mechanisms resulting in aphantasics being slower in image trials than non-aphantasics, priming through visual imagery could be used in the future to distinguish between aphantasics and non-aphantasics independently of self-reports (e.g. Zeman et al, 2015Zeman et al, , 2020, as self-report measures are rather unreliable due to the constraints of introspection (Schwitzgebel, 2002). The large uncertainty regarding self-assessment of one's own imagery abilities is also reflected in the fact that 27.7% and 28.6%, respectively, of the participants in our studies were not able to classify themselves as aphantasics or non-aphantasics with certainty.…”
Section: Discussionmentioning
confidence: 99%